Declining Risk of Sudden Death in Heart Failure - Shen, Li; Jhund, Pardeep S; Petrie, Mark C; Claggett, Brian L; Barlera, Simona; Cleland, John G.F; Dargie, Henry J; Granger, Christopher B; Kjekshus, John; Køber, Lars; Latini, Roberto; Maggioni, Aldo P; et al. (The New England journal of medicine, 2017)
Data were analyzed from 40,195 patients with heart failure with reduced ejection fraction enrolled in 12 clinical trials in the 1995–2014 period. Sudden-death rates declined substantially over time, a finding consistent with a cumulative effect of evidence-based medical therapy.